Efeitos do tratamento com formalina e sulfato de cobre sobre os parâmetros hematológicos e parasitos monogenéticos em juvenis de Hemigrammus sp. (Osteichthyes: Characidae) - Paixão, Luciana Farias; Santos, Rudã Fernandes Brandão [UNESP]; Ramos, Fabricio Menezes; Fujimoto, Rodrigo Yudi (FapUNIFESP (SciELO), 2013)
The objective of this study was to evaluate the effectiveness of formalin and copper sulphate to control monogeneans in juvenile Hemigrammus sp and its effect on leukocyte count. We used a completely randomized design with five treatments and three replications. All treatments lasted for three days and consisted of: T1, control; T2 and T3 immersion bath for one hour in formalin, an of two concentrations of 0.25 ml formalin and the other 0.1 ml L-1; the T4 bath for 24 hours with 0,025 ml of formalin-L-1; and T5, bath 24 hours with copper sulphate (0.3 mg L-1). After the experimental period was observed that T2, 100% mortality. The T3 and T5 provided 100% efficiency, however, fish presented mortalities and intoxication of the 66 and 80% respectively. T4 showed an efficacy of 77.7% and decrease in parasitological indices: total number of parasites of11, 3 ± 9, mean infection intensity of 3.2 ± 2 and a prevalence of 47.1%. As the leukocytes was observed that at T3, T4 and T5 occurred differences in the proportion of lymphocytes, monocytes and neutrophils as compared to control. The CuSO4 and formalin reduce the parasite load, but presented to be toxic at higher concentrations.
Evaluation of formalin and copper sulfate on monogenetic parasite (Urocleidoides sp.) of Hemigrammus sp. (Osteichthyes: Characidae) juveniles
Keywords: Control; CuSO4; Formalin; Monogenea